Incidence, Treatment Patterns, and Health Care Costs of Infantile Hemangioma: Results of a Retrospective German Database Analysis. Issue 4 (4th July 2017) - Seiffert, Anna; Schneider, Markus; Roessler, Jochen; Larisch, Katharina; Pfeiffer, Dunja
Abstract: Objectives: To determine the incidence, effect (defined according to treatment rate), and health care costs of infantile hemangiomas (IHs) in Germany from 2007 to 2012 by analyzing patient data of German statutory health insurances. Methods: A retrospective analysis using data from a database matched with the overall population covered by German statutory health insurance was performed. To describe the treatment rate and costs of IHs, a search algorithm was developed dividing the study population into three groups (patients with IHs, patients with IHs possibly requiring treatment, and patients with IHs receiving treatment). Results: The incidence of IHs was 2.0% to 3.2%, with a slight increase during the later years of the study period and a female:male ratio of 1.4:1. IH incidence was lower and girls were less likely to present with IHs than in previous reports. The mean treatment rate of IHs was 11.3%. Mean health care costs during first year of life for infants diagnosed with IHs in 2012 were slightly lower (€2, 396) than for all infants (€2, 649), whereas costs for infants diagnosed and treated for IHs were considerably higher (€10, 550). The majority of these costs were due to hospitalization (€8, 658). Conclusion: This retrospective study is the first to analyze the incidence and sex ratio of IHs based on German claims data. The treatment rate of IHs was consistent with previous reports. The mean health care costs for treated patients with IHs were substantially higher than those for all newborns. Limitations of this study are coding bias, a limited sample size, and claims perspective (nonclinical approach).